Crowd-induced vibrations of a steel footbridge in Reykjavík - Ingólfsson, Einar Thór; Gudmundsson, G. V.; Živanović, Stana; Pavić, Aleksandar (The Society for Experimental Mechanics, Inc., 2012)
Vibration serviceability of structures for human occupancy has become an important part of the design of slender civil engineering structures such as footbridges. In the past decades, a considerable amount of research has been carried out within the field and international codes of practice and state-of-the-art design guidelines been improved considerably. However, there are several important questions that remain unanswered. In particular the response of pedestrians to footbridge vibrations is severely under-researched. This is primarily due to lack of data from real-life footbridges subject to in-service traffic. In addition, the lack of a generally accepted way to quantify measured vibration response on footbridges makes it difficult to interpret data from already published experiments. In this paper, various methods to quantify human-response to vibrations are reviewed and put in relation to the results obtained from a controlled crowd test on a steel footbridge in Reykjavik, Iceland. A systematic quantification of the measured vibration response is carried out and the results are presented statistically through their probability distributions. Finally, testimonies from participants in a controlled perception tests are used in conjunction with measured responses, to obtain valuable information about human response to footbridge vibration. It is shown that there is only a small correlation between the subjective rating and the vibration felt by the pedestrians.